P52 Quality End of Life Care for All (QELCA©). (1st October 2013) - Bryan, Liz; Cooper, Marie; Hayes, Anita
Abstract : The Department of Health has concluded that the non-specialist workforce needs to develop the necessary attitudes and skills in order to deliver consistently high quality care for people approaching the end of life and is looking for beacons of best practice in relation to practice development initiatives (DoH, 2008). St Christopher's Hospice has designed a training programme which not only role-models end of life care to the participants but equips and empowers them to deliver better care to patients on their return to practice. QELCA© was designed to be delivered by hospice nurses to nurses working in hospitals. Teams of acute nurse clinical managers from the same department spend 5 days based at the hospice in small groups of three or four. Using the hospice setting as a learning resource, nurses are offered a first-hand experience of observing and being alongside specialist nurses as they care for patients at the end of life. In addition to this practice experience the 5-day programme combines classroom discussion and reflection facilitated by experienced specialist palliative care nurses. The programme then continues with six months facilitated Action Learning Sets (ALS) so that action plans for self, team and organisation, formulated by the participants on the final day of their hospice experience, can be supported in practice and learning from the programme consolidated. In partnership with St Christopher's and Help the Hospices, the National End of Life Care Programme (NEoLCP), through the Transform Programme (NEoLCP, 2013), piloted QELCA © across 17 sites. 21 hospices were involved and a total of 137 acute nurses attended the QELCA © programme. Evaluation data were collected at four stages across the pilot timeline using mixed methods comprising, survey questionnaires, semi-structured questionnaires and focus groups. A report outlined the findings and made recommendations for the further development of the programme.